HELICOBACTER PYLORI INFECTION IN PATIENTS WITH CALCULAR CHOLECYSTITIS: A HOSPITAL BASED STUDY - Abro, Arshad Hussain; Haider, Irfan Zafar; Ahmad, Sarfraz (Journal of Ayub Medical College Abbottabad, 2011)
Background: Helicobacter pylori, a gram negative bacillus has been recognised as a public health problem and approximately half of the world population has H. pylori infection causes chronic gastritis, peptic ulcer disease and gastric malignancies. Objective of this study was to determine the frequency of H. pylori infection in patients of chronic calcular cholecystitis. Methods: This cross-sectional descriptive study was conducted at Liaquat University Hospital, Hyderabad, Pakistan from April 2010 to September 2010. All patients with history of gallstone presented with acute abdominal pain, dyspepsia, bloating and epigastric discomfort and diagnosed as calcular cholecystitis were further evaluated for the detection of H. pylori by serology and histopathology. Frequency and percentage of H. pylori infection in patients with calcular cholecystitis was calculated. Result: Total 100 patients of cholelithiasis underwent laparoscopic cholecystectomy were recruited. The pain in upper right part of the abdomen was observed in all 100 patients, fever in 75%, nausea and vomiting in 68%, loss of appetite in 45%, feeling of tiredness or weakness in 22%, headache in 38%, chills in 52%, backache in 58%, pain under the right shoulder in 45%, heartburn in 67%, belching in 54%, indigestion in 80%, dyspepsia in 90%, bloating in 88%, and epigastric discomfort in 85% patients. Eighty-two percent patients had family history of gallstones. The mean age of overall study population was 48.72±8.78 years and mean age of H. pylori infected calcular cholecystitis patients was 47.98±5.43 years in male and 48.76±6.68 years in females. The H. pylori infection was identified in 55% patients with calcular cholecystitis, of which 32.7% were males and 67.3% were females (p=0.03, statistically significant). Majority of females (60%) had ‰¥40 U/ml antibody titre (p=0.917, non-significant). Conclusion: A possible relationship was identified between Helicobacter pylori and calcular cholecystitis Keywords: Gallstones, cholilithiasis, calcular cholecystitis, cholelithiatic cholecystitis, Helicobacter pylori